Uso de polímero hidratado na produção de palma forrageira opuntia stricta cultivar orelha de elefante mexicana - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Due to the high demand for forage availability in the agricultural production system, rural producers seek technologies adhered to local cultures. The cultivation of cactus pear combined with management technologies is justified, in order to expand and optimize cactus production with the use of hydrated polymer, which promotes efficient water absorption with gradual supply. The use of the polymer enables probable changes in the results in cactus pear production, showing a considerable improvement in the productive performance of this forage. In view of this, it was verified possible changes in physical - chemical, agronomic, productive, qualitative and quantitative characteristics that the different fertilization strategies cause forage palm. The objective of this study was to evaluate the influence of the use of hydrated polymer (hydrogel) on the production of cactus pear Opuntia stricta, cultivar Orelha de africana. The experimental design adopted was a randomized block. Three treatments with six replications were used, totaling 18 experimental units. The treatments were T1: Conventional Fertilization (FC): chemical fertilizer was applied in the traditional way; T2: Foliar Fertilization + Hydrogel (FFH), received Potassium K (KCL) + Nitrogen (urea) in liquid form via foliar, then received agricultural hydrogel via soil; T3: Foliar Fertilization without Hydrogel (FF), received Potassium K (KCL) + Nitrogen (urea) in liquid form, but in all treatments Phosphorus (P2O5), via soil. The treatments, when compared, did not have a significant influence on the morphological variables of biometrics and biomass production submitted to different fertilization strategies, so the treatment Foliar Fertilization + polymer (FFH), it is noticed that there was a contribution in improving the chemical composition attributes of the variables MM, PB and LIG. Referring to the data obtained in the present research, it can be concluded that there was an influence of the use of hydrated polymer in the production of forage palm Opuntia stricta, cultivar Orelha de Elephant mexicana, and the product allowed effect on the chemical composition of the variables PB, MM and LIG of the forage produced.
Use of hydrated polymer in the production of forage palm opuntia stricta cultivar Mexican elephant ear
Keywords: Fertilização foliar; Orelha de elefante; Palma forrageira; Polímero hidratado; Forragicultura; Foliar fertilization; Elephant ear; Forage palm; Hydrated polymer; Forage farming; CIENCIAS AGRARIAS